2021
DOI: 10.3389/fpsyg.2021.713212
|View full text |Cite
|
Sign up to set email alerts
|

Individual Faces Were Not Discarded During Extracting Mean Emotion Representations

Abstract: Individuals can perceive the mean emotion or mean identity of a group of faces. It has been considered that individual representations are discarded when extracting a mean representation; for example, the “element-independent assumption” asserts that the extraction of a mean representation does not depend on recognizing or remembering individual items. The “element-dependent assumption” proposes that the extraction of a mean representation is closely connected to the processing of individual items. The process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 42 publications
0
0
0
Order By: Relevance
“…These findings are consistent with previous results that used the member judgement task [ 17 , 45 , 46 ], which found that observers preferred to recognize the unseen average facial expression as a member of the previously presented set. However, some studies suggest that the integration of a group of facial expressions as an average representation using ensemble coding depends on the shape of the feature distribution [ 22 , 23 ], that is, observers perceive a group of cross-category facial expressions as two subsets and form two average representations separately because these crowds are perceived as two-peak distributions.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These findings are consistent with previous results that used the member judgement task [ 17 , 45 , 46 ], which found that observers preferred to recognize the unseen average facial expression as a member of the previously presented set. However, some studies suggest that the integration of a group of facial expressions as an average representation using ensemble coding depends on the shape of the feature distribution [ 22 , 23 ], that is, observers perceive a group of cross-category facial expressions as two subsets and form two average representations separately because these crowds are perceived as two-peak distributions.…”
Section: Discussionsupporting
confidence: 92%
“…As mentioned above, in the BD ensemble condition, even though probe face C (the average representation of the previously presented ensemble) was not presented in the ensemble stimuli, it was perceived as equally familiar as the actually presented probe faces (B faces and D faces), and the familiarities of these three probe faces were significantly larger than those of other unpresented probe faces (A faces and E faces). This average bias accords with previous studies regarding ensemble coding of facial expressions in a member judgement task [17,45,46], where observers tend to recognize the unseen average facial expression as a member of previous ensemble stimuli, implying that observers form an average representation when they perceive a crowd of faces automatically. However, these studies either only showed within-category crowds or did not discriminate the contributions of cross-category crowds from within-category crowds.…”
Section: Discussionsupporting
confidence: 89%